THE INFLUENCE OF THE STEP HEIGHT AND THE MUSICAL CADENCE ON THE GROUND REACTION FORCE IN TWO MOVEMENTS OF STEP TRAINING (Fiep Bulletin - online, 2014)
INTRODUCTION: The Step Training was one of the novelties in the 90s, arising from the adaptation of the Swedish bench by the Professor Gin Miller. The modality consists on going up and down a platform (step), using music to mark the rhythm. OBJECTIVE: Evaluate the implications of different music cadences (136, 140, 144 e 152 bpm) on platform heights of 10 and 20 cm over a vertical component of Ground Reaction Force (GRF) in the basic and simple knee elevation steps in descending movement. METHODOLOGY: It was used two platforms of extensometer forces, one at ground level and another at 10 and 20 cm of the ground and CDs recorded to mark the rhythm. The 5 subjects carried out 12 complete cycles of the two steps in four cadences and two analyzed heights. The data were normalized by the Corporal Weight (CW) of the subjects and the statistics were done with software Statistics version 6.0. The comparison among the values of GRF in the 4 speeds was carried out through the variant analysis test ANOVA One Way. For comparison among platform heights it was used a test "t" of Student for independent samples. RESULTS: According to table 1, the values found for GRF in the musical cadence change at the same platform height were not statistically significative to p < 0,05 in both steps. Nonetheless, the height elevation caused a significant rising (p < 0,05) on the GRF values in all studied speeds except at the height of 10 cm and musical cadence of 152 bpm.CONCLUSION: The variable platform height implied on the increasing of GRF in the descending phase of the movement inboth analyzed steps. Already, the variable execution speed was not determinant to significantly increase the GRF on platform heights studied in both steps.
Keywords: Step Training; biomechanics; Ground Reaction Force